Revitalisasi Pendidikan Agama Hindu dalam Menciptakan Budaya Religius bagi Generasi Hindu 2017 - I Nyoman Sueca (Jurnal Penjaminan Mutu, 2017)
The problem of education is an issue of human life throughout their life, both as individuals, social groups as well as members of society. A hope for the government and society to the generations of Hindu that schools of Hinduism can be built not only in formal education but through education in formal and non-formal as in the rise and pasraman-pasraman in every Pakraman in Bali, so the creation of a religious culture, the strong one. The phenomenon that occurs in the Hindu generation, where Hindu religious education in the learning process in schools to create a culture of religious solely to meet the cognitive, affective and psychomotor aspects whereas as if ignored, this happens because of the situation of globalization. Build or revitalize Hindu religious education is actually the duty of teachers and parents with instilling religious values to create a religious culture. A religious culture that is based on religion teacher jobs, selfless, is also a method for building one's values in a comprehensively manner.